The effectiveness of laserpuncture associated with vitamin B12 in the treatment of temporomandibular disorders and orofacial pain (Research, Society and Development, 2023)
A low-power laser is presented as a treatment proposal for painful Temporomandibular Disorders (TMD). This randomized clinical trial evaluated the effectiveness of laserpuncture using low power laser in the treatment of pain in patients with temporomandibular disorders with and without concomitant administration of vitamin B12 (methylcobalamin). A questionnaire was applied to the participants to assess the location of the orofacial pain in conjunction with the request for blood vitamin B12 dosage. The groups were randomly divided, being Group 1: placebo laserpuncture and placebo vitamin B12; Group 2: effective laserpuncture and placebo vitamin B12, and Group 3: effective laserpuncture and effective vitamin B12. The study consisted of 45 adult patients (over 18 years old), regardless of sex and race, with signs and symptoms of TMD, where pain was the main complaint. In all sessions, pain was assessed using a visual analogue scale, before and after laser therapy. Laserpuncture was applied to points of Traditional Chinese Medicine, used for treating Temporomandibular Disorders, using a laser device with an infrared wavelength and energy of 3J. Eight sessions were heldand two sessions per week for 4 weeks. Groups 2 and 3 showed improvement in pain symptoms after treatment. Group 3 patients in the fourth session already showed the effective result of the treatment. Laserpuncture when associated with the use of vitamin B12 becomes more efficient for treating TMD.